A Study of the Determinants of Large-Scale Financing Decision: The Case of the Pacific Alliance Countries (2021)
There are two forms of large-scale funding in the markets: bond issuance and syndicated loans. The latter have shown significant growth in recent times. Using data from Bloomberg, the determinants to decide whether getting funding from one alternative or another among 54 companies of the Pacific Alliance were investigated. Using Panel Data Models with ordinary least squares and a Probit model with random effects, it was found that factors such as the amount of credit, the sector, profitability, and the size of the firms play a significant role in the decision to get syndicated loans. Knowing the determinants to make a decision on funding is important since it allows the firm’s management to know which aspects they should consider when deciding which alternative they’d choose to finance themselves and their implications. This study constitutes a first approximation to the analysis of the syndicated loan market in the Latin America emerging countries.